Pengaruh Inflasi terhadap Konsumsi Rumah Tangga di Indonesia - Islah Sahbana Kudadiri; Nazwa Aurelia Sinaga (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study is to identify and analyze the effects of inflation on household consumption in Indonesia. Thus, the focus on the dynamics of people's spending is based on basic needs and non-smoking. This study uses a descriptive qualitative approach enhanced by secondary data from macroeconomic literature and primary data in the form of national statistical reports published by the Central Bureau of Statistics (BPS). This analysis is carried out based on the concept of Keynes' consumption theory, Friedman's permanent income hypothesis, and Modigliani's life cycle theory. The results show that increasing inflation has a significant impact on lower household consumption. In particular, the low group with moderate sorting shows a large allocation of income for basic needs. Groups with higher incomes through alternative strategies or delayed consumption tend to be more adaptable. These results suggest that price control policies and social security networks are strengthened as an effort to maintain consumption stability in the budget. This summary includes the background, objectives, methods, results, and conclusions related to explaining the actual conditions and political impacts of the relationship between Indonesian inflation and household consumption.